Cuestión de Ética (2013)
Within organizations it is customary to choose as coordinator, boss, manager or supervisor of a work team, that person who, regularly, is the closest to the address. Most of the time, you do not have the required experience that would enrich the work environment, if not, you get to learn in practice, leading to expenses and demotivation in employees, who do not consider it fair that this character is in that position, having people with the skills, abilities and knowledge that are needed.